RETRACTED: Strategi Pemasaran Destinasi Wiasata Arung Jeram Ranau Desa Rantau Nipis Kec.Banding Agung Oku Selatan - Afta Apriansyah Afta; Muhammad Renaldi; Mardian Hari Pratama; Desy Misnawati (Communicator Sphere, 2022)
This paper has been found to be in violation of Communicator Sphere publication ethic principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in Jurnal Ilmu Komunikasi, Vol. 1, No. 2 (2022), URL: https://journal.yp3a.org/index.php/mukasi/article/view/705, entitled "Strategi Pemasaran Destinasi Wisata Arung Jeram Ranau Desa Rantau Nipis Kec. Banding Agung Oku Selatan". The document and its content has been removed from Communicator Sphere, and reasonable effort should be made to remove all references to this article.